ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN TERHADAP PRODUK FAST FASHION DI INDONESIA - Rahmat Purbandono Hardani (LPPM STIE YKPN Yogyakarta, 2023)
Fast fashion is a fashion product that is produced in a short period of time and at a low price, every season fast fashion is able to produce more than 1 fashion of clothing such as summer or winter clothes with various modes. Based on the Industry Ranking on fastretailing.com, the fast fashion industry is controlled by 3 big players, namely INDITEX (ZARA), UNIQLO, and H&M. This research aims to examine the influence of brand awareness on consumer buying interest, the influence of product quality on consumer buying interest, the influence of product price on consumer buying interest, and the influence of promotions on potential consumers' buying interest. The research results show that the four variables above partially have a positive and significant influence on consumer buying interest in fast fashion products.